What is the Best Clinical Test for Assessment of the Teres Minor in Massive Rotator Cuff Tears? - Collin, Philippe (Clin Orthop Relat Res, 2015)
BACKGROUND: Few studies define the clinical signs to evaluate the integrity of teres minor in patients with massive rotator cuff tears. CT and MRI, with or without an arthrogram, can be limited by image quality, soft tissue density, motion artifact, and interobserver reliability. Additionally, the ill-defined junction between the infraspinatus and teres minor and the larger muscle-to-tendon ratio of the teres minor can contribute to error. Therefore, we wished to determine the validity of clinical testing for teres minor tears. QUESTION/PURPOSES: The aim of this study was to determine the accuracy of commonly used clinical signs (external rotation lag sign, drop sign, and the Patte test) for diagnosing the teres minor’s integrity. METHODS: We performed a prospective evaluation of patients referred to our shoulder clinic for massive rotator cuff tears determined by CT arthrograms. The posterosuperior rotator cuff was examined clinically and correlated with CT arthrograms. We assessed interobserver reliability for CT assessment and used three different clinical tests of teres minor function (the external rotation lag sign, drop sign, and the Patte test). One hundred patients with a mean age of 68 years were available for the analysis. RESULTS: The most accurate test for teres minor dysfunction was an external rotation lag sign greater than 40°, which had a sensitivity of 100% (95% CI, 80%–100%) and a specificity of 92% (95% CI, 84%–96%). External rotation lag signs greater than 10° had a sensitivity of 100% (95% CI, 80%–100%) and a specificity of 51% (95% CI, 40%–61%). The Patte sign had a sensitivity of 93% (95% CI, 70%–99%) and a specificity of 72% (95% CI, 61%–80%). The drop sign had a sensitivity of 87% (95% CI, 62%–96%) and a specificity of 88% (95% CI, 80%–93%). An external rotation lag sign greater than 40° was more specific than an external rotation lag sign greater than 10° (p < 0.001), and a Patte sign (p < 0.001), but was not more specific than the drop sign (p < 0.47). There was poor correlation between involvement of the teres minor and loss of active external rotation. CONCLUSIONS: Clinical signs can predict anatomic patterns of teres minor dysfunction with good accuracy in patients with massive rotator cuff tears. This study showed that the most accurate test for teres minor dysfunction is an external rotation lag sign and that most patients’ posterior rotator cuff tears do not lose active external rotation. Because imaging is not always accurate, examination for integrity of the teres minor is important because it may be one of the most important variables affecting the outcome of reverse shoulder arthroplasty for massive rotator cuff tears, and the functional effects of tears in this muscle on day to day activities can be significant. Additionally, teres minor integrity affects the outcomes of tendon transfers, therefore knowledge of its condition is important in planning repairs. LEVEL OF EVIDENCE: Level III, diagnostic study.